Analisis Soal Cerita Matematika pada Materi Bangun Datar Kelas IV Sekolah Dasar - Shela Anggraeni; Viktor Pandra; Lucy Arsi Purwasih (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This research aims to determine the quality of mathematics story questions in grade IV elementary school flat figures and find out how to prepare good mathematics story questions in grade IV elementary school. The method used in this research is a case study. The books analyzed in this research are